WOPN을 동반한 급성 괴사성 췌장염 환자에서 내시경적 췌장괴사 제거술 후 발생한 Wernicke Encephalopathy 1예 - 김민수; 강은경; 김수영; 김지연; 문송미; 서일혜; 조재희; 박윤수; Minsu Kim; Eun Kyung Kang; Su Young Kim; Ji-Yeon Kim; et al. (Korean journal of pancreas and biliary tract, 2016)
Infected walled-off pancreatic necrosis (WOPN) is dangerous complication of acute pancreatitis. Open necrosectomy and post-operative irrigation of necrotic cavity have been conventional treatment for infected pancreatic necrosis, however, recently minimally invasive techniques such as endoscopic necrosectomy has been regarded as preferred treatment method for infected WOPN. Endoscopic necrosectomy provides a targeted approach with a reduction in the systemic inflammatory response and avoidance of wound complications. Non alcohol related Wernicke encephalopathy is rare disease caused by thiamine deficiency due to intravenous feeding, and presented an encephalopathy, oculomotor dysfunction, gait ataxia. We report herein a case of Wernicke encephalopathy after successful endoscopic necrosectomy for infected WOPN.